W 2 B 5 / C composite material and preparation method thereof
Through the solid solution structure and hot press sintering technology of W2B5/C composite materials, the problems of carbon materials at high temperature oxidation and uneven dispersion of ceramic phases are solved, and the high strength and oxidation resistance are improved and process simplified. It is suitable for high-temperature application scenarios .
Patent Information
- Application Number
- CN202411332049.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-24
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2044-09-24
AI Technical Summary
Carbon materials are easily oxidized under high-temperature oxygen-containing atmosphere, resulting in reduced mechanical properties. In addition, traditional carbon materials have problems of uneven dispersion of ceramic phases and difficult processing when improving their oxidation resistance, which makes it difficult to meet the needs of high-end product fields.
Using W2B5/C composite material, solid solution is formed through W2B5 and C, which enhances the bonding strength between the ceramic phase and the carbon phase, and through hot pressing reaction sintering technology, W2B5 is uniformly distributed to enhance the phase, reduce porosity, improve the mechanical properties of the material and anti-oxidation. performance.
It significantly improves the mechanical properties and oxidation resistance of the material, simplifies the preparation process, reduces costs, and is suitable for high-temperature application scenarios such as heating bodies and mold release molds, expanding the application scope of composite materials.
Smart Images

Figure CN118834069B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of ceramic composite materials, and in particular relates to a W2B5 / C composite material and a preparation method thereof. Background Art
[0002] Carbon is one of the most widely distributed basic elements in nature. It exists widely in the form of simple substance or compound structure, from amorphous non-crystalline state to highly crystalline graphite state. Different structural characteristics show different comprehensive properties, such as self-lubrication, low thermal expansion rate, good electrical conductivity, thermal conductivity, chemical corrosion resistance, wear resistance and other excellent properties. In addition, carbon materials also have unique advantages such as low density, air permeability, high melting point, heat shock resistance, low thermal expansion, low linear expansion coefficient and easy finishing. They are widely used in various fields, such as sealing materials, electrical engineering, metallurgy, smelting electrodes, acid and alkali resistant heat exchangers, heating molds, melting metal crucibles, etc. Therefore, carbon materials are regarded as indispensable and important materials in modern industry and have become a key direction in the field of materials research.
[0003] Although carbon materials have a wide range of applications, they are susceptible to oxidation under high-temperature oxygen-containing atmosphere conditions, which causes the material matrix structure to be severely damaged and the mechanical properties to be reduced, limiting the scope of use of carbon materials. However, with the continuous development of modern industrial fields, traditional carbon materials can no longer meet the growing industry needs, especially for high-end product fields, such as high-strength hot pressing molds, high-temperature and oxidation-resistant heating elements, and crucibles for smelting high-temperature metals. In addition to high strength and high modulus, carbon materials must also have certain antioxidant capabilities. Therefore, how to improve the high-temperature antioxidant properties of carbon materials is of great significance to the development and application of carbon materials.
[0004] In the prior art, by compounding SiC, B4C or TiC and other ceramic components in the carbon material matrix, the mechanical properties of the carbon material can be improved to a certain extent, and the thermal conductivity of the carbon material can also be improved. However, such materials are often added in a high amount, all above 30 vol.%, which leads to a high hardness of the material and difficulty in processing. Moreover, due to the high content of the ceramic phase, thermal shock cracking is easily caused during the heating process, and it is not suitable for some special fields, such as heating elements, demolding molds, hot bending molds and other industries. For boride ceramics, the chemical compatibility with the carbon material matrix is the best, the linear expansion coefficient is close, and the tungsten atoms have a high valence electron concentration, which can be combined with boron by covalent bonds to form transition metal borides. The self-diffusion coefficient between crystal atoms is high, and the sintering performance of the material is good. It is an ideal carbon material reinforcement phase, which has excellent effects on mechanical properties, oxidation resistance, and thermal and electrical conductivity. However, the traditional process often has the problem that the ceramic phase is difficult to disperse evenly in the carbon matrix, and the price is relatively expensive, the process is relatively difficult, and the mechanical properties are slightly poor, and the effect is not ideal. Summary of the invention
[0005] In view of the deficiencies in the prior art, the object of the present invention is to provide a W2B5 / C composite material, in which W2B5 and C form a solid solution, which enhances the bonding strength between the ceramic phase and the carbon phase, thereby improving the mechanical properties of the material. At the same time, the W2B5 / C composite material uses the carbon phase as a continuous matrix, effectively isolates the W2B5 particles, reduces the adhesion between the ceramic phases, and W2B5 is uniformly distributed on the carbon phase surface or in the gap as a reinforcing phase, which not only strengthens the interfacial bonding force, but also reduces the porosity. In particular, W2B5 exhibits excellent spreading and wetting ability on the carbon phase interface, promotes close bonding between the interfaces, makes the composite material structure more uniform and dense, thereby achieving a significant improvement in overall performance.
[0006] Another object of the present invention is to provide a method for preparing a W2B5 / C composite material, which has a simple process and is easy to control.
[0007] The preparation method of the W2B5 / C composite material of the present invention comprises the following steps:
[0008] (1) Mixing reaction carbon, tungsten carbide, boron carbide and ball milling dispersant, ball milling and drying to obtain composite powder;
[0009] (2) The composite powder is placed in a graphite mold and subjected to hot pressing reaction sintering to obtain a solid solution ceramic containing a carbon phase and a ceramic phase, namely, a W2B5 / C composite material; wherein the content of W2B5 accounts for 10-30 vol.% of the total amount of the W2B5 / C composite material;
[0010] The overall reaction equation of tungsten carbide and boron carbide is as follows:
[0011] ;
[0012] The step-by-step reaction equation of tungsten carbide and boron carbide is as follows:
[0013] ;
[0014] ;
[0015] .
[0016] The total volume of the W2B5 / C composite material is the sum of the total volumes of the reaction carbon, W2B5 and the generated carbon.
[0017] The reaction carbon is calcined petroleum coke (density 2.2g / cm 3 ) or flake graphite (density 2.2g / cm 3 );
[0018] The density of the tungsten carbide is 15.7 g / cm 3 , the density of boron carbide is 2.5g / cm 3 ;
[0019] The ceramic phase in the W2B5 / C composite material is W2B5, and the density is 11.2 g / cm 3 ; The carbon phase is the reaction carbon and the generated carbon (density is 2.2g / cm 3 )'s mixture.
[0020] In the tungsten carbide and boron carbide, the molar ratio of tungsten element to boron element is (0.3~0.5):1.
[0021] The particle size of the reaction carbon is 1-30 μm.
[0022] The particle size of the tungsten carbide and boron carbide is 1-20 μm.
[0023] The ball milling dispersant is anhydrous ethanol.
[0024] The ratio of the amount of the ball mill dispersant to the total amount of the reaction carbon, tungsten carbide and boron carbide is (100-150): 100 mL / g.
[0025] In the step (1), the rotation speed of the ball mill is 80-120 r / min and the time is 12-24 h.
[0026] In the step (2), the temperature of hot pressing reaction sintering is 1800-2000°C, the pressure is 20-30 MPa, and the time is 0.5-1 h.
[0027] The W2B5 / C composite material is prepared by the above-mentioned method for preparing the W2B5 / C composite material.
[0028] Compared with the prior art, the present invention has the following beneficial effects:
[0029] (1) The present invention introduces the ceramic phase W2B5 into the carbon-based material. Compared with traditional boride ceramics, the tungsten material is inexpensive and has a high valence electron concentration. Moreover, W2B5 is a transition metal boride bonded by covalent bonds, with a high self-diffusion coefficient between crystal atoms and good sintering performance. The prepared composite material has excellent performance. The B element in the W2B5 system can form a solid solution with C, increasing the bonding strength between the ceramic phase and the carbon phase, thereby improving the mechanical properties of the material;
[0030] (2) The W2B5 / C composite material of the present invention uses the carbon phase as a continuous matrix phase, which can prevent the ceramic phases W2B5 from contacting each other and limit the adhesion between the ceramic phases W2B5. W2B5, as a reinforcing phase, is uniformly coated on the surface of the carbon phase or filled in the gaps between the carbon phase particles, thereby improving the interfacial bonding between the composite matrix and reducing the porosity of the composite material. For the interface of the composite material, W2B5, as a reinforcing phase, exhibits excellent spreading and wetting ability on the carbon phase interface, effectively promoting the close bonding between the carbon phase interfaces, making the interface between the matrix particles more and more blurred, which is more conducive to the sintering and densification of the composite material, making the organizational structure of the composite material more uniform and dense.
[0031] (3) The preparation method of the W2B5 / C composite material described in the present invention adopts hot pressing reaction sintering technology, combines hot pressing sintering and reaction sintering, and applies external force during the reaction sintering process of the material, which can promote the sintering densification of the material. Compared with traditional reaction sintering, the preparation method described in the present invention can promote the in-situ generation of the reinforcing phase directly inside the matrix, ensuring excellent compatibility, uniform distribution and strong bonding between the reinforcing phase and the matrix; at the same time, the preparation method simplifies the production process, eliminating multiple steps such as synthesis, pretreatment, mixing and compounding of composite powders, which not only shortens the process flow, but also significantly reduces the process cost;
[0032] (4) The W2B5 / C composite material described in the present invention is a low-ceramic phase composite material. The proportion of the ceramic phase W2B5 is relatively low, only 10~30vol.%, but it has the advantages of good strength, oxidation resistance, ablation resistance, good processability, thermal shock resistance, etc. It is suitable for some special fields, such as heating elements, demolding molds, hot bending molds and other industries, which expands the application range of composite materials and solves the problems of sintering difficulties and difficult molding in the preparation process of low-ceramic composite materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 This is a surface electron microscope image of the W2B5 / C composite material prepared in Example 1 (×5000);
[0034] Figure 2 This is a cross-sectional electron micrograph of the W2B5 / C composite material prepared in Example 1 (×5000 times);
[0035] Figure 3 This is a surface electron microscope image of the W2B5 / C composite material prepared in Example 2 (×5000);
[0036] Figure 4 This is a cross-sectional electron micrograph of the W2B5 / C composite material prepared in Example 2 (×5000 times);
[0037] Figure 5This is a surface electron microscope image of the W2B5 / C composite material prepared in Example 3 (×5000);
[0038] Figure 6 This is a cross-sectional electron micrograph of the W2B5 / C composite material prepared in Example 3 (×5000 times);
[0039] Figure 7 This is a surface electron microscope image of the W2B5 / C composite material prepared in Example 4 (×5000);
[0040] Figure 8 This is a cross-sectional electron micrograph of the W2B5 / C composite material prepared in Example 4 (×5000 times);
[0041] Fig. 9 This is a surface electron microscope image of the W2B5 / C composite material prepared in Example 5 (×5000);
[0042] Fig.10 This is a cross-sectional electron micrograph of the W2B5 / C composite material prepared in Example 5 (×5000 times);
[0043] Fig.11 This is a surface electron microscope image of the W2B5 / C composite material prepared in Example 6 (×5000);
[0044] Fig.12 This is a cross-sectional electron micrograph of the W2B5 / C composite material prepared in Example 6 (×5000);
[0045] Fig.13 This is a surface electron microscope image of the composite material prepared in Comparative Example 1 (×5000 times);
[0046] Fig.14 This is a cross-sectional electron microscope image of the composite material prepared in Comparative Example 1 (×5000 times);
[0047] Fig.15 This is a surface electron microscope image of the composite material prepared in Comparative Example 2 (×5000 times);
[0048] Fig.16 This is a cross-sectional electron micrograph of the composite material prepared in Comparative Example 2 (×5000 times);
[0049] Fig.17 This is an electron microscope image of the crack propagation path of the W2B5 / C composite material prepared in Example 3 (×500);
[0050] Fig.18 The electron microscope image (×500 times) of the crack propagation path of the composite material prepared in Comparative Example 1;
[0051] Fig.19This is an electron microscope image (×500 times) of the crack propagation path of the composite material prepared in Comparative Example 2. DETAILED DESCRIPTION
[0052] The present invention will be further described below with reference to the embodiments.
[0053] The raw materials used in the examples and comparative examples are conventional commercially available raw materials unless otherwise specified, and the process methods used in the examples and comparative examples are conventional methods in the art unless otherwise specified.
[0054] Example 1
[0055] The preparation method of the W2B5 / C composite material comprises the following steps:
[0056] (1) 34 g of tungsten carbide (particle size 1 μm), 6 g of boron carbide (particle size 1 μm), 60 g of calcined petroleum coke (particle size 1 μm) and 150 mL of anhydrous ethanol were mixed and ball milled. The grinding balls were zirconia balls with a diameter of 6 mm. The ball-to-material ratio was 2:1. The speed of the ball milling was 120 r / min. The time was 24 h. After the ball milling, the mixture was dried and passed through an 80-mesh sieve to obtain a composite powder.
[0057] (2) The composite powder is placed in a graphite mold and subjected to hot pressing reaction sintering in a sintering furnace. The hot pressing reaction sintering temperature is 2000°C, the pressure is 30 MPa, and the time is 0.5 h. After sintering, the composite powder is cooled and taken out of the furnace to obtain a W2B5 / C composite material, in which the content of W2B5 accounts for 10 vol.% of the total amount of the W2B5 / C composite material.
[0058] The surface and cross-sectional morphology of the W2B5 / C composite material were observed by scanning electron microscopy. Figure 1~2 shown.
[0059] Figure 1 The surface electron microscope image of the W2B5 / C composite material prepared in Example 1 is shown in FIG. Figure 1 It can be seen that when the content of W2B5 in the composite material is 10 vol.%, there are fine pores on the surface of the composite material.
[0060] Figure 2 This is a cross-sectional electron micrograph of the W2B5 / C composite material prepared in Example 1. Figure 2 It can be seen that the fracture surface of the composite material is relatively rough and uneven, the fracture path is relatively tortuous, and the fracture mode is brittle fracture.
[0061] Example 2
[0062] The preparation method of the W2B5 / C composite material comprises the following steps:
[0063] (1) 44 g of tungsten carbide (particle size of 10 μm), 8 g of boron carbide (particle size of 10 μm), 48 g of calcined petroleum coke (particle size of 5 μm) and 150 mL of anhydrous ethanol were mixed and ball-milled. The grinding balls were zirconia balls with a diameter of 6 mm. The ball-to-material ratio was 2:1. The speed of the ball milling was 80 r / min for 24 h. After the ball milling, the mixture was dried and passed through an 80-mesh sieve to obtain a composite powder.
[0064] (2) The composite powder is placed in a graphite mold and subjected to hot pressing reaction sintering in a sintering furnace. The hot pressing reaction sintering temperature is 2000°C, the pressure is 30 MPa, and the time is 0.5 h. After sintering, the composite powder is cooled and taken out of the furnace to obtain a W2B5 / C composite material, in which the content of W2B5 accounts for 15 vol.% of the total amount of the W2B5 / C composite material.
[0065] Figure 3 This is the surface electron microscope image of the W2B5 / C composite material prepared in Example 2. Figure 3 It can be seen that the carbon phase is a continuous matrix phase, showing a lamellar structure, and W2B5, as a reinforcing phase, is evenly coated on the surface of the carbon phase or filled in the gaps between the carbon phase particles, improving the interfacial bonding strength between the composite matrix and reducing the porosity of the composite.
[0066] Figure 4 This is a cross-sectional electron micrograph of the W2B5 / C composite material prepared in Example 2. Figure 4 It can be seen that the cross section is smooth and flat, which is a transgranular fracture, while the edge of the grain is uneven, and the fracture mode gradually transitions from a simple transgranular fracture to a mixed mode of transgranular fracture and intergranular fracture.
[0067] Example 3
[0068] The preparation method of the W2B5 / C composite material comprises the following steps:
[0069] (1) 44 g of tungsten carbide (particle size of 5 μm), 8 g of boron carbide (particle size of 5 μm), 24 g of calcined petroleum coke (particle size of 15 μm), 24 g of flake graphite (particle size of 15 μm) and 150 mL of anhydrous ethanol were mixed and ball milled. The grinding balls were zirconia balls with a diameter of 6 mm. The ball-to-material ratio was 2:1. The speed of the ball milling was 120 r / min for 24 h. After the ball milling, the mixture was dried and passed through an 80-mesh sieve to obtain a composite powder.
[0070] (2) The composite powder is placed in a graphite mold and subjected to hot pressing reaction sintering in a sintering furnace. The hot pressing reaction sintering temperature is 2000°C, the pressure is 30 MPa, and the time is 0.5 h. After sintering, the composite powder is cooled and taken out of the furnace to obtain a W2B5 / C composite material, in which the content of W2B5 accounts for 15 vol.% of the total amount of the W2B5 / C composite material.
[0071] Figure 5 This is the surface electron microscope image of the W2B5 / C composite material prepared in Example 3. Figure 5 It can be seen that there are more isolated large particles in the calcined petroleum coke, and there are more holes and cracks on the surface. After adding flake graphite, some large pores can be filled. When the pores between the large particles are filled, new small pores also appear. At this time, W2B5 compensates for it, and the small-sized pores are significantly reduced, achieving an excellent stacking system. There are no cracks and large pores on the surface of the composite material, and the porosity is low.
[0072] Figure 6 This is a cross-sectional electron micrograph of the W2B5 / C composite material prepared in Example 3. Figure 6 It can be seen that through the grading effect between calcined petroleum coke and flake graphite, the mixing law is satisfied, the particle structure in the carbon phase matrix is uniform and dense, and the composite effect of grading plays an important role. A bridge bond structure that absorbs the expansion of microcracks is formed inside, reducing the expansion of cracks, which is beneficial to the improvement of the flexural strength of the composite material.
[0073] Example 4
[0074] The preparation method of the W2B5 / C composite material comprises the following steps:
[0075] (1) 52 g of tungsten carbide (particle size of 15 μm), 9 g of boron carbide (particle size of 15 μm), 39 g of calcined petroleum coke (particle size of 20 μm) and 150 mL of anhydrous ethanol were mixed and ball-milled. The grinding balls were zirconia balls with a diameter of 6 mm. The ball-to-material ratio was 2:1. The ball-milling speed was 100 r / min for 24 h. After the ball-milling, the mixture was dried and passed through an 80-mesh sieve to obtain a composite powder.
[0076] (2) The composite powder is placed in a graphite mold and subjected to hot pressing reaction sintering in a sintering furnace. The hot pressing reaction sintering temperature is 2000°C, the pressure is 30 MPa, and the time is 0.5 h. After sintering, the composite powder is cooled and taken out of the furnace to obtain a W2B5 / C composite material, in which the content of W2B5 accounts for 20 vol.% of the total amount of the W2B5 / C composite material.
[0077] Figure 7 This is the surface electron microscope image of the W2B5 / C composite material prepared in Example 4. Figure 7 It can be seen that with the increase of W2B5 content, the adhesion of the ceramic phase becomes stronger and stronger, and the pores become smaller and smaller.
[0078] Figure 8 This is a cross-sectional electron micrograph of the W2B5 / C composite material prepared in Example 4. Figure 8It can be seen that due to the effect of W2B5, the carbon phase undergoes slow plastic flow, which makes the pores in the matrix gradually smaller, the microstructure more dense, and the mechanical strength of the composite material is greatly improved.
[0079] Example 5
[0080] The preparation method of the W2B5 / C composite material comprises the following steps:
[0081] (1) 58 g of tungsten carbide (particle size 20 μm), 10 g of boron carbide (particle size 20 μm), 32 g of calcined petroleum coke (particle size 5 μm) and 100 mL of anhydrous ethanol were mixed and ball milled. The grinding balls were zirconia balls with a diameter of 6 mm. The ball-to-material ratio was 2:1. The ball milling speed was 120 r / min for 12 h. After the ball milling, the mixture was dried and passed through an 80-mesh sieve to obtain a composite powder.
[0082] (2) The composite powder is placed in a graphite mold and subjected to hot pressing reaction sintering in a sintering furnace. The hot pressing reaction sintering temperature is 1800°C, the pressure is 25 MPa, and the time is 1 h. After the sintering is completed, the composite powder is cooled and taken out of the furnace to obtain a W2B5 / C composite material, in which the content of W2B5 accounts for 25 vol.% of the total amount of the W2B5 / C composite material.
[0083] Fig. 9 This is the surface electron microscope image of the W2B5 / C composite material prepared in Example 5. Fig. 9 It can be seen that the composite material has a smooth surface, a dense structure, and fewer pores. The carbon phase sheets are completely flat, the sheets overlap each other, and the layers are stacked on each other. The W2B5 particles are dispersed between the carbon phase sheets, forming an embedded and embedded structure, filling the pores in the graphite matrix. The carbon phase and W2B5 have good sintering bonding with each other.
[0084] Fig.10 This is a cross-sectional electron micrograph of the W2B5 / C composite material prepared in Example 5. Fig.10 It can be seen that with the pullout of plate-like grains and lamellar carbon phase grains, cracks will deflect or bridge along the grain boundaries during the expansion process to consume the amount and improve the toughness of the composite material.
[0085] Example 6
[0086] The preparation method of the W2B5 / C composite material comprises the following steps:
[0087] (1) 63 g of tungsten carbide (particle size 3 μm), 11 g of boron carbide (particle size 3 μm), 26 g of calcined petroleum coke (particle size 30 μm) and 150 mL of anhydrous ethanol were mixed and ball-milled. The grinding balls were zirconia balls with a diameter of 6 mm. The ball-to-material ratio was 2:1. The speed of the ball milling was 120 r / min for 12 h. After the ball milling, the mixture was dried and passed through an 80-mesh sieve to obtain a composite powder.
[0088] (2) The composite powder is placed in a graphite mold and subjected to hot pressing reaction sintering in a sintering furnace. The hot pressing reaction sintering temperature is 1800°C, the pressure is 20 MPa, and the time is 1 h. After the sintering is completed, the composite powder is cooled and taken out of the furnace to obtain a W2B5 / C composite material, in which the content of W2B5 accounts for 30 vol.% of the total amount of the W2B5 / C composite material.
[0089] Fig.11 This is the surface electron microscope image of the W2B5 / C composite material prepared in Example 6. Fig.11 It can be seen that W2B5 significantly reduces the gaps between particles and effectively fills the pores between particles. From the cross section, it can be seen that there are fewer gaps between the carbon phase particles, the coating is better, the structure is uniform, and the density is high.
[0090] Fig.12 This is a cross-sectional electron micrograph of the W2B5 / C composite material prepared in Example 6. Fig.12 It can be seen that the internal structure of the composite material is uniform and dense, and the crack propagation during the fracture process mainly occurs on the particle interface with weak bonding. There are a large number of cleavage sections with blurred boundaries, indicating that a good interface bonding has been formed between W2B5 and the carbon phase.
[0091] Comparative Example 1
[0092] The difference from Example 2 is that an equal amount of calcined petroleum coke is replaced by carbon black, and the rest is the same as Example 2.
[0093] Fig.13 This is the surface electron microscope image of the composite material prepared in Comparative Example 1. Fig.13 It can be seen that during the hot pressing reaction sintering process, carbon black as a carbon phase material has poor plastic flow ability, the pores in the matrix are difficult to migrate and discharge, and the lamellar structure is also easy to accumulate with each other to form pores, resulting in a low density of the composite material.
[0094] Fig.14 The cross-sectional electron micrograph of the composite material prepared in Comparative Example 1 is shown in FIG. Fig.14 It can be seen that the presence of a large number of pore defects leads to weak bonding between the composite matrix, prone to brittle fracture, and exhibits low flexural strength at the macro level.
[0095] Comparative Example 2
[0096] The difference from Example 3 is that the particle sizes of the tungsten carbide, boron carbide, calcined petroleum coke and flake graphite used are all 35 μm, and the rest are the same as Example 3.
[0097] Fig.15 This is the surface electron microscope image of the composite material prepared in Comparative Example 2. Fig.15 It can be seen that due to improper grading size, flake graphite has a large aspect ratio. During the hot pressing process, flake graphite tends to be oriented in a direction perpendicular to the hot pressing, and the layers are stacked on each other. The calcined petroleum coke cannot fill into the pores to make up for the large pores. The stratification phenomenon is obvious, resulting in poor bonding and larger pores.
[0098] Fig.16 The cross-sectional electron micrograph of the composite material prepared in Comparative Example 2 is shown in FIG. Fig.16 It can be seen that due to the poor grading effect between the raw materials, the internal structure of the composite material is relatively loose, there are more independent layers at the fracture, the interface bonding is poor, the boundary is clearly visible, and the strength is low.
[0099] The crack propagation paths of the composite materials prepared in Example 3, Comparative Example 1 and Comparative Example 2 were observed by scanning electron microscopy. The results are as follows: Figures 17 to 19 As shown, Fig.18 This is the crack direction of Comparative Example 1. Since the reaction carbon is carbon black, the interface bonding is weak, the crack extends along the interface between the carbon phase and W2B5, and the crack length is short. Fig.19 The crack direction of comparative example 2 is shown in the figure. It can be seen from the figure that the crack begins to deflect, but due to improper particle size grading, the crack is still relatively short and the strength is slightly lower. Fig.17 The crack direction of Example 3 can be seen from the figure that the propagation path of the crack of the W2B5 / C composite material is relatively tortuous, and a step-like fracture morphology appears on the fracture surface. When the material is damaged, transgranular fracture occurs. Protruding lamellae appear between the calcined petroleum coke particles, which shows that graphite is pulled out when the material breaks, which reveals that intergranular fracture occurs when the material breaks, promoting crack deflection, thereby consuming more fracture energy and achieving the purpose of toughening.
[0100] Comparative Example 3
[0101] The difference from Example 6 is that 84 g of tungsten carbide (particle size 3 μm), 15 g of boron carbide (particle size 3 μm), 5 g of carbon black (particle size 20 μm) and 150 mL of anhydrous ethanol are mixed, wherein the content of W2B5 accounts for 60 vol.% of the total amount of the W2B5 / C composite material, and the rest is the same as Example 6.
[0102] The composite materials obtained in Examples 1 to 6 and Comparative Examples 1 to 3 were subjected to performance tests, and the test methods were as follows:
[0103] Bulk density (g / cm 3 ): The Archimedes method of displacement was used to determine the bulk density of the composite material. An analytical balance with an accuracy of 0.01 mg was used to determine the weight of the composite material in air and the floating weight in water. The density calculation formula is as follows:
[0104] ;
[0105] Where ρ is the bulk density of the composite material (g / cm 3 ), m1 is the weight of the dry composite sample in air (g), ρ1 is the density of water (g / cm 3 ), m2 is the weight of the sample after immersion in water (g).
[0106] Density (%): The ratio of the volume density of the composite material to the theoretical density. The calculation formula of the theoretical density is as follows: ;
[0107] In the formula, ρ c is the theoretical density (g / cm 3 ), ρ i is the theoretical density of the i-th phase (g / cm 3 ), V i is the volume fraction of the ith phase (%).
[0108] Flexural strength (MPa): Tested in accordance with GB / T 6569-2006;
[0109] Fracture toughness (MPa·m 1 / 2 ): Tested in accordance with GB / T 23806-2009;
[0110] Vickers hardness (GPa): Tested in accordance with GB / T 16534-2009;
[0111] Resistivity (Ω·m): The resistivity of the sample is measured using a digital four-probe tester with a measurement range of 1×10 -6 ~2×10 6 Ω·cm;
[0112] Graphitization degree (%): The interplanar spacing of the sample was measured by X-ray diffractometer, and the graphitization degree was calculated by the following formula:
[0113] ;
[0114] Where: g is the graphitization degree of the sample, d is 002 is the face distance.
[0115] The test results are shown in Table 1.
[0116] Table 1 Performance test results
[0117]
[0118] It can be seen from Table 1 that for W2B5 / C composite materials, as the content of W2B5 increases, the flexural strength, fracture toughness, Vickers hardness and other properties of the composite materials also increase continuously, and the resistivity gradually decreases. This is mainly because: when the content of W2B5 begins to increase, the density of the material and the bonding strength between W2B5 and the carbon phase also gradually increase. While improving the flexural strength of the material, the fracture toughness is also improved at the same time. At the same time, W2B5 can play a role in passivating the crack tip extension and promoting crack deflection, thereby inducing delamination toughening, effectively improving the external additional fracture energy, and enhancing the performance of the composite material.
[0119] By comparing Example 2 with Comparative Example 1, it can be seen that due to the different reactive carbon materials, the density of the W2B5 / C composite material is also different, among which the composite material prepared from the easily graphitized calcined petroleum coke has higher performance. Different reactive carbons have different sintering activities. The easily graphitized reactive carbon has a large reaction activity with B4C and WC particles, and it is easy to generate a reaction interface with higher activity, thereby promoting the reaction and sintering between particles. Carbon black belongs to a hard carbon material. The introduction of hard carbon materials will lead to a low density of the composite material, which also has an important impact on the performance of the composite material.
[0120] By comparing Example 3 with Comparative Example 2, it can be seen that different particle size gradations also have an important influence on the W2B5 / C composite material, where the large particle size plays the role of a large particle skeleton in the green body structure, which is used to improve the thermal shock resistance of the composite material and reduce defects such as thermal stress cracking during the sintering process. The medium particle size is used to fill the gaps between large particles, reducing large pores into small pores, and the fine particle size plays the role of a small particle binder, further reducing small pores, while reducing cracks generated during the sintering process and increasing mechanical strength. The use of different particle sizes can effectively improve the density of the composite material and enhance the overall performance of the material. However, due to improper gradation size in Comparative Example 2, the mutual filling between particles is poor, and the pores are difficult to close, which in turn affects its performance.
[0121] It can be seen from Example 6 and Comparative Example 3 that the W2B5 / C composite material prepared by the present invention can maintain the performance advantage of a high carbon phase at a low ceramic phase content, compared with the traditional composite material prepared using a high content of carbon black as the reaction carbon. Moreover, on this basis, through material design and preparation technology, the performance is further optimized and improved, thereby expanding its application field.
Claims
1. A method for preparing a W2B5 / C composite material, characterized in that: The following steps are involved: (1) Mixing reaction carbon, tungsten carbide, boron carbide and ball milling dispersant, ball milling and drying to obtain composite powder; (2) The composite powder is placed in a graphite mold and subjected to hot pressing reaction sintering to obtain a W2B5 / C composite material; wherein the content of W2B5 accounts for 10-25 vol.% of the total amount of the W2B5 / C composite material; The reaction carbon is calcined petroleum coke or flake graphite; The particle size of the reaction carbon is 1-30 μm; The particle size of the tungsten carbide and boron carbide is 1-20 μm; In the tungsten carbide and boron carbide, the molar ratio of tungsten element to boron element is (0.3-0.5):1; The ball milling dispersant is anhydrous ethanol; In the step (2), the temperature of hot pressing reaction sintering is 1800-2000°C and the pressure is 20-30MPa; In the step (2), the hot pressing reaction sintering time is 0.5 to 1 hour.
2. The method for preparing the W2B5 / C composite material according to claim 1, characterized in that: The ratio of the amount of the ball mill dispersant to the total amount of the reaction carbon, tungsten carbide and boron carbide is (100-150): 100 mL / g.
3. The method for preparing the W2B5 / C composite material according to claim 1, characterized in that: In the step (1), the rotation speed of the ball mill is 80-120 r / min and the time is 12-24 h.
4. A W2B5 / C composite material, characterized in that: The W2B5 / C composite material is prepared by the preparation method of any one of claims 1 to 3.
